Hayek's treatment of legal positivism - Daniel Nientiedt (Duke University, Center for the History of Political Economy (CHOPE), 2020)
Friedrich Hayek devoted the later part of his career to investigating the legal rules required for the existence of a free society. The subject of this paper is Hayek's treatment of legal positivism, which he thought was the most important intellectual movement responsible for the decline of liberal institutions in Europe in the early 20th century. As shown in the paper, Hayek's critique consists of two separate arguments: that legal positivism destroys the rule of law and that it amounts to constructivism. The first claim rests on the assumption that "true" laws comply with the rule of law principle, although the meaning of the adjective true is ambiguous. The second claim holds only for a particular variant of legal positivism. In addition to discussing these issues, the paper provides an assessment of Hayek's own evolutionary theory of law, which was intended as an alternative to both legal positivism and natural law theory.
Keywords: 330